Pengaruh E-WOM (Electronic Word Of Mouth), Costumer Behavior, And Trust Terhadap Keputusan Pembelian Konsumen Pada Gloryal Kosmetik Praya - Tanthowi, Muhammad; Basalamah, Muhammad Ridwan; Rahmawati, Rahmawati (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research discusses the influence of E-WOM (Electronic Word Of Mouth), Costumer Behavior, And Trust Regarding Consumer Purchasing Decisions on Gloryal Cosmetics Praya. Gloryal cosmetics itself is a shop engaged in marketing cosmetic products which was founded in 2018. This type of research is quantitative research with data collection techniques through distributing questionnaires and data analysis techniques, namely multiple linear regression statistical analysis. The population used in this research is consumers from the city of Praya who have purchased products from Gloryal Cosmetics, the number of which is of course unknown. The samples used were 75 samples based on the Malhotra formula. Based on the results of research conducted by researchers in selecting objects, Gloryal Cosmetics is one of the shops referred to by the public for shopping for cosmetics. Based on the results of research that has been carried out, the E-WOM variable (Electronic Word Of Mouth), costumer behavior, and trust influence simultaneously or partially on consumer purchasing decisions. Keywords: E-WOM (Electronic Word Of Mouth), Costumer Behavior, Trust, Purchasing Decisions.